MOLECULAR CHARACTERIZATION OF LOCALLY ADOPTED SUGARCANE (Saccharum officinarum L.) VARIETIES USING MICROSATELLITE MARKERS - M. S. Ahmed; S. D. A. Gardezi (Journal of Animal and Plant Sciences, 2017)
Sugarcane is an important crop that caters about 80 percent sugar requirement of the world. Modern day cultivated sugarcane is a complex hybrid between its few species like Saccharum officinarum L.and S. spontaneum L.having complex aneuploidy genomes with almost eight sets of basic chromosome number. Its flowering behaviours in the country and use of setts as seed narrow downs its genetic base. Molecular characterization provides the basis for determining its variability to start reasonable breeding program. Microsatellite markers have the unique ability to determine the extent of genetic divergence among sugarcane genotypes. In present study 49 SSR primers were utilized for selection of genetically diverse genotypes among 20 sugarcane cultivars adopted in Pakistan. A total of 420 bands were generated with a size range from 50 bp to 600 bp. The total number of bands generated by single primers pair ranged from 3 to 22. Polymorphic information contents (PIC) estimated ranged from 0.7 to 0.3. Cluster analysis grouped genotypes into four distinctive clusters at 70% genetic homology. Principal Coordinate analysis generated 50.04% variation from first 4 PCoA, of which PCoA-1 and PCoA-2 accounted 31% variability. PCoA divided genotypes into 4 groups in a similar pattern as generated with cluster analysis and authenticated the results of cluster analysis. Four genotypes viz; S-03-US-694, S-05-FSD-307, S-08-FSD-19 and HSF-240 were selected for future breeding endeavours involving crossing between genotypes that may provide valuable strategies for pyramiding beneficial gene(s) in novel sugarcane cultivars. It is concluded that use of SSR marker is very reliable approach for identification of diverse genotype(s) where phenotypic similarity of the cultivars leads to difficulty while selections of parents for hybridization.
Keywords: Genetic diversity; Sugarcane; SSR markers; PAGE; Cluster analysis; Principal Coordinate Analysis